Medio Siglo de publicaciones botánicas en la Revista de Biología Tropical - León, Jorge (Universidad de Costa Rica, 2002)
Over its first half century the Revista de Biología Tropical published many papers and supplements dealing with the botany. However, the Revista is not a primary botanical journal. A wide variety of topics and geographic sources have been included, taking into consideration species from the Neotropics, but also from India and Nigeria. A complete index of botanical papers is presented